Statutory rights and duties of the parties under the Malaysian Moneylenders Law. - Muhammad Arif, Afida Mastura; Parry, Deborah (World Business Institute, 2008)
This article will consider the aspects of reform brought by the Malaysian Moneylenders (Amendment) Act 2003 in regard to the statutory rights and duties of the borrower and the moneylender under the moneylending transaction. Such rights and duties, which are derived from the moneylenders law and the moneylending agreement will be analysed to determine whether they are adequate to protect the interest of the borrowers, and whether the reform under the 2003 Act has addressed the weaknesses under the old law in strengthening the position of the borrowers in the moneylending transaction.